EXTREME-SCALE COMPUTING--WHERE 'JUST MORE OF THE SAME' DOES NOT WORK. - Hoisie, Adolfy; Getov, Vladimir (Computer (00189162), 2009)
The article focuses on the direct relation of extreme-scale computing with simulations of unprecedented size and accuracy and with the development of computing ideas. The growing complexity in the field is reportedly demanding faster processing. It is stated that questions like the limits to manageable levels of parallelism and to the number of cores in building a computer are being asked by professionals. A preview of articles on the subject published within the issue is also given.